2001
DOI: 10.1038/90373
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The ubiquitin conjugating enzyme complex Mms2-Ubc13 plays a key role in post-replicative DNA repair in yeast and the NF-kappaB signal transduction pathway in humans. This complex assembles novel polyubiquitin chains onto yet uncharacterized protein targets. Here we report the crystal structure of a complex between hMms2 (Uev1) and hUbc13 at 1.85 A resolution and a structure of free hMms2 at 1.9 A resolution. These structures reveal that the hMms2 monomer undergoes a localized conformational change upon interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(95 citation statements)
references
References 28 publications
3
92
0
Order By: Relevance
“…Recently, McKenna et al (33) showed that in human cells, hMms2 forms a complex with hUbc13, and this interaction is required for hUbc13-mediated polyubiquitination through Lys-63. The crystal structure of this complex also was determined recently (34). Our data support the hypothesis that the hMms2͞hUbc13 complex is required to recruit or activate proteins needed by human cells to be able to make use of an undamaged homologous copy of DNA as an alternative template to avoid fork-blocking lesions and continue DNA replication.…”
Section: Indirect Evidence That Human Cells Use the Newly Synthesizedsupporting
confidence: 70%
“…Recently, McKenna et al (33) showed that in human cells, hMms2 forms a complex with hUbc13, and this interaction is required for hUbc13-mediated polyubiquitination through Lys-63. The crystal structure of this complex also was determined recently (34). Our data support the hypothesis that the hMms2͞hUbc13 complex is required to recruit or activate proteins needed by human cells to be able to make use of an undamaged homologous copy of DNA as an alternative template to avoid fork-blocking lesions and continue DNA replication.…”
Section: Indirect Evidence That Human Cells Use the Newly Synthesizedsupporting
confidence: 70%
“…Recently, the high-resolution x-ray crystal structures of both the human (45) and S. cerevisiae (38) Ubc13/Mms2 heterodimer have been solved, and both structures propose models that could accommodate the active site tethered and noncovalently bound Ub molecules. In combination with the data presented in this manuscript, these structures establish a foundation for the assembly of Lys-63 chains by the Ubc13/Mms2 heterodimer.…”
Section: Discussionmentioning
confidence: 99%
“…The UEV Domains Share a Common Fold but Use This Fold to Make Diverse Interactions-The structure of the Vps23 UEV domain has an overall fold that is similar to the two other structurally characterized UEV domains, human Tsg101 (54) and Mms2 (56,57) (Fig. 5, A and B).…”
Section: Both Unique and Commonly Exploited Ub Surfaces Interact Withmentioning
confidence: 99%
“…5B; Refs. 56,57). Similarly, the S1-S2 loop of Ubc13 interacts with Mms2, and the bound Mms2 covers a surface of Ubc13 analogous to the Vps23 UEV surface interacting with Ub (Fig.…”
Section: Both Unique and Commonly Exploited Ub Surfaces Interact Withmentioning
confidence: 99%